2006
DOI: 10.1095/biolreprod.105.045138
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, Gene Modification, and Nuclear Reprogramming of Porcine Mesenchymal Stem Cells1

Abstract: Bone marrow mesenchymal stem cells (MSCs) are adult pluripotent cells that are considered to be an important resource for human cell-based therapies. Understanding the clinical potential of MSCs may require their use in preclinical large-animal models, such as pigs. The objectives of the present study were 1) to establish porcine MSC (pMSC) cultures; 2) to optimize in vitro pMSC culture conditions, 3) to investigate whether pMSCs are amenable to genetic manipulation, and 4) to determine pMSC reprogramming pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
134
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(151 citation statements)
references
References 54 publications
14
134
1
2
Order By: Relevance
“…Multilineage differentiation potential of isolated porcine MSCs was evaluated by culturing the second-passage MSCs (3 · 10 4 cells/cm 2 in 35-mm dish) with osteogenic or adipogenic induction medium for 3 weeks, as previously described (Bosch et al, 2006). Briefly, for osteogenic induction, differentiation media were replaced every 3-4 days; for adipogenic differentiation, cells were first exposed to induction medium for 3 days and then cultured in maintenance medium for another 1 days.…”
Section: In Vitro Induction Of Mesenchymal Lineage Differentiation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Multilineage differentiation potential of isolated porcine MSCs was evaluated by culturing the second-passage MSCs (3 · 10 4 cells/cm 2 in 35-mm dish) with osteogenic or adipogenic induction medium for 3 weeks, as previously described (Bosch et al, 2006). Briefly, for osteogenic induction, differentiation media were replaced every 3-4 days; for adipogenic differentiation, cells were first exposed to induction medium for 3 days and then cultured in maintenance medium for another 1 days.…”
Section: In Vitro Induction Of Mesenchymal Lineage Differentiation Ofmentioning
confidence: 99%
“…The transgenic efficiency was 0.37% (data not reported yet), which is slightly lower than that associated with the Yorkshire MSCs showed in this study. Two previous studies indicated that cultured MSCs can undergo transient as well as stable genetic modification by nonviral and viral vectors (Bosch et al, 2006;Colleoni et al, 2005), but production of genetically engineered cloned pigs from MSCs was not reported in these two studies. During the preparation of this manuscript, a research group reported that they used MSCs to generate gene-targeted pig models through the SCNT technique Leuchs et al, 2012).…”
mentioning
confidence: 96%
“…These stem cells are capable of differentiating into various cellular lineages, including the osteogenic, chondrogenic, adipogenic, and myogenic lineages (Pittenger et al, 1999;Jiang et al, 2002;Imabayashi et al, 2003;Bosch et al, 2006), and are widely used in clinical investigations (Friedenstein et al, 1966;Horwitz et al, 2002;Kadivar et al, 2006;Yang et al, 2008). Before human clinical trials can be approved, scaled-up cell production and delivery into an animal model with cell doses (number of cells) comparable to those anticipated for human trials are often required in order to satisfy regulatory safety concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have reported the characterization and differentiation of porcine somatic stem cells [1][2][3][4][5][6][7][8][9][10]. The generation of oocytes from somatic stem cells in vitro may provide a valuable model for identifying factors involved in germ cell formation and oocyte differentiation.…”
mentioning
confidence: 99%